Excel Data Analysis - Guerrero, Hector (Springer, 2019)
Why Does the World Need—Excel Data Analysis, Modeling, and Simulation? When spreadsheets first became widely available in the early 1980s, it spawned a revolution in teaching. What previously could only be done with arcane software and large-scale computing was now available to the common man, on a desktop. Also, before spreadsheets, most substantial analytical work was done outside the classroom where the tools were; spreadsheets and personal computers moved the work into the classroom. Not only did it change how the data analysis curriculum was taught, but it also empowered students to venture out on their own to explore new ways to use the tools. I can’t tell you how many phone calls, office visits, and/or emails I have received in my teaching career from ecstatic students crowing about what they have just done with a spreadsheet model. I have been teaching courses related to business and data analytics and modeling for over 40 years, and I have watched and participated in the spreadsheet revolution. During that time, I have been a witness to the following important observations: • Each successive year has led to more and more demand for Excel-based analysis and modeling skills, both from students, practitioners, and recruiters. • Excel has evolved as an ever more powerful suite of tools, functions, and capabilities, including the recent iteration and basis for this book—Excel 2013. • The ingenuity of Excel users to create applications and tools to deal with complex problems continues to amaze me. • Those students who preceded the spreadsheet revolution often find themselves at a loss as to where to go for an introduction to what is commonly taught to most undergraduates in business and sciences.
Modeling and Simulation